Cross-dehydrogenative coupling of acetanilides with aromatic aldehydes. (27th February 2020) - Kianmehr, Ebrahim; Afaridoun, Hadi
Abstract : A practical, versatile, and efficient method for N -acylation of acetanilides with aromatic aldehydes, benzyl halides, benzyl alcohols and toluenes as the acylating agents has been described. Abstract : Potassium bromide mediated cross-dehydrogenative coupling of acetanilides with aromatic aldehydes in the presence of tert -butyl hydroperoxide (TBHP) for the synthesis of imides has been developed. This new and efficient approach was carried out under an air atmosphere at room temperature and the desired products were obtained in good to high yields.